Preservation of ∼12-h ultradian rhythms of gene expression of mRNA and protein metabolism in the absence of canonical circadian clock - Zhu, Bokai; Liu, Silvia (Frontiers in Physiology, 2023)
Introduction: Besides the ∼24-h circadian rhythms, ∼12-h ultradian rhythms of gene expression, metabolism and behaviors exist in animals ranging from crustaceans to mammals. Three major hypotheses were proposed on the origin and mechanisms of regulation of ∼12-h rhythms, namely, that they are not cell-autonomous and controlled by a combination of the circadian clock and environmental cues, that they are regulated by two anti-phase circadian transcription factors in a cell autonomous manner, or that they are established by a cell-autonomous ∼12-h oscillator. Methods: To distinguish among these possibilities, we performed a post hoc analysis of two high temporal resolution transcriptome dataset in animals and cells lacking the canonical circadian clock. Results: In both the liver of BMAL1 knockout mice and Drosophila S2 cells, we observed robust and prevalent ∼12-h rhythms of gene expression enriched in fundamental processes of mRNA and protein metabolism that show large convergence with those identified in wild-type mice liver. Bioinformatics analysis further predicted ELF1 and ATF6B as putative transcription factors regulating the ∼12-h rhythms of gene expression independently of the circadian clock in both fly and mice. Discussion: These findings provide additional evidence to support the existence of an evolutionarily conserved 12-h oscillator that controls ∼12-h rhythms of gene expression of protein and mRNA metabolism in multiple species.